Interactive Bead Necklace Customization System (IBNCS) - Albert, Lee Kok Soon (Universiti Malaysia Sarawak, (UNIMAS), 2005)
The bead necklaces produced by the residents of Bario-the Kelabits, have a high value. Kelabit are known of their skilful talent in making the valuable bead necklace which is reputed for high value because of the painstaking beadwork done by them. Interactive Bead Necklace Customization System (IBNCS) assists in promoting the unique bead necklace made by the Kelabit there. Interactive Bead Necklace Customization System (IBNCS) focuses on the capability of enabling the people from all around the world to customize their own bead necklace online provided they are equipped with internet connection IBNCS can accept customization request to make bead necklace that fits the customers' specific budget, taste and needs. IBNCS helps to preserve the cultural heritage of the Kelabit as well because this system includes a gallery that consists of photographs of Kelabit bead necklaces. The information of the beads which are included in this Interactive Bead Necklace Customization System (IBNCS) will provide a semi-virtual visualization of Bario's uniqueness - the bead necklace, to the viewers. Information about the bead necklace and the designs available are clearly stated and indicated in the system